The Hajj Ministry and the Politics of Religious Capital in Indonesia - Ayuni, Qurrata; Febriyanto, Satrio; Charles Simabura; Nurizal Ismail (Universitas Islam Negeri Raden Intan Lampung, 2026)
The establishment of the Ministry of Hajj and Umrah (Kemenhaj) in 2025 raises important constitutional questions. Within Indonesia’s non-confessional state framework, the relationship between state and religion appears to be shaped more by economic considerations than by ideological commitments. This paper suggests that state regulation of the Hajj may serve purposes beyond the spiritual welfare of pilgrims, potentially reflecting a broader logic in which worship is positioned as a form of capital. This argument is developed through three lines of inquiry. First, the state’s selective engagement with sharī’ah by regulating economically significant practices such as Hajj and zakat, while leaving private acts of worship like prayer unregulated, points to a predominantly economic rationale. Second, the substantial funds managed by BPKH (Rp171 trillion), its mega-project in Mecca in collaboration with Danantara, and a Rp34.5 trillion investment partnership with Saudi Arabia’s Public Investment Fund suggest that Hajj governance has increasingly taken on the characteristics of state-managed enterprise. Third, the creation of a religion-specific ministry raises concerns about institutional inequality, potential fragmentation, and fiscal fairness, particularly regarding the use of public funds from taxpayers of all faiths to support an institution serving Muslims exclusively. Drawing on doctrinal legal research, this paper concludes that the formalization of Hajj governance may reflect not only a commitment to serving the ummah, but also an accumulation of religious capital that warrants closer scholarly attention